Nilai Keikhlasan: Analisis Isi Program Reality Show Pantang Ngemis di GTV - Putri, Fitri Ariana; Riyadi, Agus (Jurnal Komunikasi Islam, 2021)
Television reality show programs do not only provide entertainment for the audience, but they are also oriented towards the internalisation of socio-cultural and religious values. Accordingly, many studies of da’wah lately have tried to discuss Islamic values depicted on television programs or other mass media. This article analyses the value of sincerity contained in the reality show Pantang Ngemis on Global television (GTV). A qualitative research methods and content analysis approach of Krippendorf model used in this study. The findings indicate that the internalization of the sincerity values conveyed by this program encompass the value of lillahi ta’ala, the value of high social care, living calmly, being light in doing good, and being grateful for the blessings of Allah Swt.